World englishes and English language teaching: a pragmatic and humanistic approach - Bhowmik, Subrata Kumar (Colombian Applied Linguistics Journal, 2015)
Seidlhofer (2005) describes the current status of English as an “unstable equilibrium.” In many ways this analogy regarding the current state of affairs with English language teaching (ELT) is appropriate. Taking a World Englishes (WE) perspective, this paper presents various mismatches between teaching goals and objectives vis-à-vis the teaching and learning outcomes in ELT. The paper then makes the argument that in order for more successful English language teaching and learning to take place, a pragmatic and humanistic approach needs to be adopted. An outline of such an approach is discussed.